1997
DOI: 10.1097/00003246-199709000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pediatric intensive care at six centers in Mexico and Ecuador

Abstract: For six pediatric ICUs in Mexico and Ecuador, mortality was significantly higher than predicted among lower-risk patients. Tracheal intubation, central catheters, pneumonia, sepsis, and nonsurgical status were associated with poor outcome for low-risk groups. We speculate that reducing the use of invasive central catheters and endotracheal intubation for lower-risk patients, coupled with improved infection control, could lower mortality rates in the population studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 11 publications
3
29
1
3
Order By: Relevance
“…Infants and preschool-aged children between the ages of 1 and 4 years were most frequently admitted, which is similar to results found in previous studies (8)(9)(10)(15)(16)(17)(18) . The overall mortality rate in the current study was 1.85%, which is both lower (8)(9)(15)(16)(17)(18)(19) and similar (11) to the (20) , although more recent studies have reported mortality rates below 5% (11) , and these differences emphasize the need for the collection of continuous and localized measurements. The average age of the patients who died at the PICC was 8.9 years, which is higher than that reported by Sands et al (3.1 years of age), although the quartile in this study ranged from 0.61 to 10.6 years of age.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Infants and preschool-aged children between the ages of 1 and 4 years were most frequently admitted, which is similar to results found in previous studies (8)(9)(10)(15)(16)(17)(18) . The overall mortality rate in the current study was 1.85%, which is both lower (8)(9)(15)(16)(17)(18)(19) and similar (11) to the (20) , although more recent studies have reported mortality rates below 5% (11) , and these differences emphasize the need for the collection of continuous and localized measurements. The average age of the patients who died at the PICC was 8.9 years, which is higher than that reported by Sands et al (3.1 years of age), although the quartile in this study ranged from 0.61 to 10.6 years of age.…”
Section: Discussionsupporting
confidence: 89%
“…The average age of the patients who died at the PICC was 8.9 years, which is higher than that reported by Sands et al (3.1 years of age), although the quartile in this study ranged from 0.61 to 10.6 years of age. Similar to the results of a study in the UK, neoplasms were the primary diagnosis for most of the children who died in the PICC (19) , whereas a study by Earle et al found that pneumonia was the main cause of death among patients in PICUs in Mexico and Ecuador (18) . This study analyzed the epidemiological data of patients who were admitted to the PICC at HIAE and compared these findings to those of other studies published in the literature.…”
Section: Discussionsupporting
confidence: 71%
“…In a French multicentric study, the percentage of children requiring mechanical ventilation was 64 %, central venous catheterization 42 % and arterial catheterization 23 %. These findings were higher than those found in the present study, probably due to the inclusion of more severe pathology, as evidenced by a mortality of 13 % ± double that found in this study [16,17].…”
Section: Discussioncontrasting
confidence: 85%
“…This can be achieved by well-equipped and well-staffed intensive care units. 1,2 But despite all measures, ICU is one of the sites where medical errors are most likely to occur because of the complexity of the diseases, and multiple interventions. 3,4 With the advancement in intensive care facilities, there is a dramatic increase in survival of critically ill children.…”
Section: Introductionmentioning
confidence: 99%